Evaluation of the Focused Offender Disposition Program in Birmingham, Phoenix, and Chicago, 1988-1992 - Hepburn, John R. ([Verlag nicht ermittelbar], 1999)
The Drug Testing Technology/Focused Offender Disposition (FOD) program was designed to examine two issues regarding drug users in the criminal justice system: (1) the utility of need assessment instruments in appropriately determining the level of treatment and/or supervision needed by criminal offenders with a history of drug use, and (2) the use of urinalysis monitoring as a deterrent to subsequent drug use. This data collection consists of four datasets from three sites. The FOD program was first established in Birmingham, Alabama, and Phoenix, Arizona, in December 1988 and ran through August 1990. The Chicago, Illinois, program began in October 1990 and ended in March 1992. These first three programs studied probationers with a history of recent drug use who were not incarcerated while awaiting sentencing. The subjects were assessed with one of two different treatment instruments. Half of all clients were assessed with the objective Offender Profile Index (OPI) created by the National Association of State Alcohol and Drug Abuse Directors (NASADAD). The other half were assessed with the local instrument administered in each site by Treatment Alternatives to Street Crime (TASC), Inc. Regardless of which assessment procedure was used, offenders were then randomly assigned to one of two groups. Half of all offenders assessed by the OPI and half of the offenders assessed by the local instrument were assigned to a control group that received only random urinalysis monitoring regardless of the drug treatment intervention strategy prescribed by the assessment instrument. The other half of offenders in each assessment group were assigned to a treatment group that received appropriate drug intervention treatment. The Phoenix pilot study (Part 4), which ran from March 1991 to May 1992, was designed like the first Phoenix study, except that the sample for the pilot study was drawn from convicted felons who were jailed prior to sentencing and who were expected to be sentenced to probation. These data contain administrative information, such as current offense, number of arrests, number of convictions, and prior charges. The need assessment instruments were used to gather data on clients' living arrangements, educational and vocational backgrounds, friendships, history of mental problems, drug use history, and scores measuring stakes in conformity. In addition, the study specifically collected information on the monitoring of the clients while in the FOD program, including the number of urinalyses administered and their results, as well as the placement of clients in treatment programs. The files also contain demographic information, such as age, race, sex, and education.